Answer: AOB
This is because angle AOB on top adds with BOC down below to get the largest angle AOC. See the diagram below.
When we Simplify [(x^2)^3 × 5x] / [6x^2 × 15x^3], the result obtained is (1/18)x^2
<h3>Data obtained from the question</h3>
- [(x^2)^3 × 5x] / [6x^2 × 15x^3]
- Simplification =?
<h3>How to simplify [(x^2)^3 × 5x] / [6x^2 × 15x^3]</h3>
[(x^2)^3 × 5x] / [6x^2 × 15x^3]
Recall
(M^a)^b = M^ab
Thus,
(x^2)^3 = x^6
- [(x^2)^3 × 5x] / [6x^2 × 15x^3] = [x^6 × 5x] / [6x^2 × 15x^3]
Recall
M^a × M^b = M^(a+b)
Thus,
x^6 × 5x = 5x^(6 + 1) = 5x^7
6x^2 × 15x^3] = (6×15)x^(2 + 3) = 90x^5
- [x^6 × 5x] / [6x^2 × 15x^3] = 5x^7 / 90x^5
Recall
M^a ÷ M^b = M^(a - b)
Thus,
5x^7 ÷ 90x^5 = (5÷90)x^(7 - 5) = (1/18)x^2
Therefore,
- [(x^2)^3 × 5x] / [6x^2 × 15x^3] = (1/18)x^2
Learn more about algebra:
brainly.com/question/2768008
#SPJ1
<span>Pick two pairs: 4x - 3y + z = - 10. 2x + y + 3z = 0. ... Eliminate the same variable from each system: 4x - 3y + z = - 10. 2x + y + 3z = 0. ... Solve the system of the two new equations: -5y - 5z = - 10. 5y - 7z = 34. ... Substitute into one of the original equations: - x + 2y - 5z = 17. ... <span>Check: Does 2(1) + 4 + 3(- 2) = 0 ? Yes.</span></span>
Sry but I don’t know the answer I just have two answer 2 questions so I don’t have to watch a video
Answer:
the answer is on google
Step-by-step explanation: